2001
DOI: 10.1055/s-2001-15105
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the control of gonadotrophin secretion by neurotransmitters during sexual development in rats

Abstract: Gonadotrophin hormone releasing hormone (GnRH) is the primary messenger involved in sexual maturation and the onset of puberty. The activity of these neurons are controlled by several neurotransmitters systems. The onset of puberty implies changes from a prepubertal type of gonadotrophin secretion, characterized by a low activity of GnRH neurons, to an adult pattern of secretion with phasic and synchronous activation of GnRH neurons resulting in an increase in the amplitute and frequency of GnRH pulses. Neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…Areas that contain TIP39 neurons are involved in sexual (Coolen et al, 2004;Holstege et al, 2003) and maternal functions (Li et al, 1999;Lin et al, 1998), suggesting that TIP39 may be as well. Nociception (Hamm and Knisely, 1988), hearing (Geal-Dor et al, 1993), endocrine functions (Eden, 1979;Moguilevsky and Wuttke, 2001) and clearly sexual functions (Lamming, 1994), undergo profound postnatal development in the rat. Bearing in mind that TIP39's homologue, PTHrP, has well-established effects on the development of many tissues (Kronenberg et al, 1998) and that TIP39 can affect the proliferation of some cell types in vitro (Misiano et al, 2003), the transient expression of TIP39 during postnatal development suggests that this peptide may be involved in developmental aspects of the above mentioned brain functions.…”
Section: Potential Functions Of Tip39mentioning
confidence: 99%
“…Areas that contain TIP39 neurons are involved in sexual (Coolen et al, 2004;Holstege et al, 2003) and maternal functions (Li et al, 1999;Lin et al, 1998), suggesting that TIP39 may be as well. Nociception (Hamm and Knisely, 1988), hearing (Geal-Dor et al, 1993), endocrine functions (Eden, 1979;Moguilevsky and Wuttke, 2001) and clearly sexual functions (Lamming, 1994), undergo profound postnatal development in the rat. Bearing in mind that TIP39's homologue, PTHrP, has well-established effects on the development of many tissues (Kronenberg et al, 1998) and that TIP39 can affect the proliferation of some cell types in vitro (Misiano et al, 2003), the transient expression of TIP39 during postnatal development suggests that this peptide may be involved in developmental aspects of the above mentioned brain functions.…”
Section: Potential Functions Of Tip39mentioning
confidence: 99%
“…Following earlier reports that implicated serotonin in the development and migration of GnRH neurons (Pronina et al 2003), a great deal of attention has become focused on the role of serotonin in GnRH release (Moguilevsky & Wuttke 2001, Wada et al 2006. The demonstration of synaptic contacts between the serotoninergic system and the GnRH neurons suggested that serotonin could act directly on GnRH release.…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of GnRH is modulated by neurotransmitters (Moguilevsky & Wuttke 2001), catecholamines (Becu-Villalobos & Libertun 1995), and neuropeptides (Woller et al 1992). Within the hypothalamus, the auto-regulatory control of GnRH neural activity is integrated with other hormonal inputs to provide a more complex control system.…”
Section: Introductionmentioning
confidence: 99%
“…No such studies have been done in prepubertal females. However, a review by Moguilevsky & Wuttke (2001) discusses evidence showing that catecholaminergic effects on the HPG axis display qualitative changes over the pubertal period. First, GABAergic systems have a stimulatory effect before puberty, which becomes inhibitory by adulthood.…”
Section: Discussionmentioning
confidence: 99%